Outcome of fallopian tube recanalization - Gautam, Jageshwor (Nepal Journal of Obstetrics and Gynaecology, 2008)
Objective: To find out the fertility outcome of tubal surgery. Method: This was a hospital based descriptive study conducted at Om Hospital, Bharatpur. Forty-one women who were operated in this hospital during the period of 6 years. (Jan 2002- December 2007). Results: Of 41 patients who underwent tuboplasty, 34 (82.9%) cases were available for follow-up. Out of these 34 cases, 14 (41.2%) became pregnant. Among them 9 (64.3%) had viable births, 3 (21.4%) ectopic pregnancies and 2 (14.3%) spontaneous miscarriages. Conclusion: Fallopian tube recanalization has been established as an effective, useful and novel treatment of infertility due to tubal occlusion. Key words: Infertility, fallopian tube, tuboplasty, pregnancy.   doi:10.3126/njog.v3i1.1439 NJOG 2008 May-June; 3(1): 43 - 45